ANALISIS KOMPARASI HASIL BELAJAR MAHASISWA PRODI PENDIDIKAN EKONOMI REGULER DAN PPAPK FKIP UNIVERSITAS TANJUNGPURA - Isma Dewi; Bambang Genjik Sutomo; Thomy Sastra Atmaja (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to determine the differences in learning outcomes between students of Regular Economic Education and PPAPK, Teaching and Education Faculty, Tanjungpura University. The research method used is comparative description. The data sources of this research are the Regular and PPAPK students. This study collected data from the students' Grade Point Average (GPA). The research data was analyzed using descriptive statistical analysis techniques. Testing the research hypothesis using the t-test which shows that, 1) the average student learning outcomes of 3.61, 2) learning outcomes of PPAPK students an average of 3.26. Based on the results of hypothesis testing using independent samples T-test, it shows that the value of t count 7.060> t table 1.671 and the value of Sig. (2-tailed) 0.00 <0.05, indicating that Ha is accepted and H0 is rejected, so it can be concluded that there is a significant difference in learning outcomes of students in the Regular Economic Education Study Program and PPAPK. The difference is due to several factors, namely internal factors (student motivation, intelligence, concentration, health or physical condition) and external factors (professional and personal abilities of lecturers, the role of parents, learning environment, learning time, and student activity outside of lectures).Keywords: Learning Outcomes, PPAPK Students, and Regular Students.